Effectiveness of Simulator-Based Training for Cataract Surgery in Postgraduate Ophthalmology Residents: Doi: 10.36351/pjo.v42i1.2220 - Ahmad, Imran; Mahsood, Yousaf Jamal (Pakistan Journal of Ophthalmology, 2025)
Purpose: To compare the impact of virtual reality–based cataract surgery training versus conventional patient-based training on surgical performance, confidence, and self-efficacy among postgraduate residents. Study Design: Quasi experimental study. Place and Duration of Study: A multicentered study conducted from October 2023 to March 2024. Methods: Thirty-two second-year FCPS trainees were enrolled and divided equally into two groups. The simulator-trained group practiced cataract surgical steps on a virtual reality simulator and progressed to real patients only after achieving ≥60% accuracy in each step. The conventional group received traditional training through the master-apprenticeship model, starting surgical steps on cataract patientsunder supervision. Both groups were later assessed while performing cataract surgery under consultant supervision using a structured proforma. Results: Simulator-trained trainees performed significantly better in basic steps such as incision and paracentesis, viscoelastic injection, and initiation of Capsulorhexis (p = 0.028, 0.042, and 0.050, respectively). No statistically significant difference was observed in more advanced steps, including Capsulorhexis completion (p = 0.11), hydro-dissection (p = 0.60), phacoemulsification (p= 0.57–0.72), nucleus manipulation (p = 0.68), cortex removal (p = 0.81), intraocular lens placement (p = 0.48), and wound closure (p = 0.27). Simulator-based trainees outperformed in 3 of 13 steps, while differences in the remaining steps were not significant. Conclusion: Simulator training improves basic cataract skills but not advanced maneuvers; it is a useful adjunct for early skill acquisition.